2015
DOI: 10.1111/jsm.12952
|View full text |Cite
|
Sign up to set email alerts
|

The International Society for Sexual Medicine's Process of Care for the Assessment and Management of Testosterone Deficiency in Adult Men

Abstract: Introduction In 2014, the International Society for Sexual Medicine (ISSM) convened a panel of experts to develop an evidence-based process of care for the diagnosis and management of testosterone deficiency (TD) in adult men. The panel considered the definition, epidemiology, etiology, physiologic effects, diagnosis, assessment and treatment of TD. It also considered the treatment of TD in special populations and commented on contemporary controversies about testosterone replacement therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
130
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 130 publications
(180 reference statements)
0
130
0
Order By: Relevance
“…The Canadian guideline advises a threemonth trial of treatment, 1 as also recommended in the Endocrine Society guideline. 5 In line with the International Society for Sexual Medicine guideline, 3 I suggest that clinicians consider a minimum period of six months when assessing response. In a randomized controlled trial of testosterone undecanoate in men with type 2 diabetes, my colleagues and I showed that improvement continued until six months, and even extended to 12 months in some patients.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The Canadian guideline advises a threemonth trial of treatment, 1 as also recommended in the Endocrine Society guideline. 5 In line with the International Society for Sexual Medicine guideline, 3 I suggest that clinicians consider a minimum period of six months when assessing response. In a randomized controlled trial of testosterone undecanoate in men with type 2 diabetes, my colleagues and I showed that improvement continued until six months, and even extended to 12 months in some patients.…”
mentioning
confidence: 97%
“…Given the ongoing controversy and changes in our understanding of testosterone deficiency, it is not surprising that there are multiple guidelines available from other developers, including recent updates from the European Association of Urology 2 and the International Society for Sexual Medicine. 3 The guideline from the Canadian Men's Health Foundation 1 provides recommendations specifically for Canadian physicians and is largely consistent with the 2008 International Society for the Study of the Aging Male 4 and 2010 Endocrine Society guidelines. 5 The current guideline will be a useful resource for Canadian physicians, but although research studies are bringing clarity to some aspects of caring for patients with testosterone deficiency syndrome, there are still many for which there is no consensus.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Testosterone therapy is appropriate for treating ED, particularly at TT levels <8nmol/L, 4,7 and for salvaging ED treatment failures with oral medication, particularly at TT levels <10.4 nmol/L. 24 It also reduces the need for more invasive and expensive second-and third-line ED treatments in …”
Section: Testosterone Therapymentioning
confidence: 99%
“…5 The condition is characterised by a deficiency in serum androgen levels, with or without decreased genomic sensitivity to androgens, 6 and relevant signs and symptoms. 5,7 Epidemiology of TD There is wide variation in the estimated prevalence of TD. The European Male Aging study evaluated more than 3000 men between 40-79 years of age according to biochemistry and symptoms, defining the syndrome of TD as the presence of three or more sexual symptoms associated with a total testosterone (TT) level less than 11 nmol/L, and a free testosterone (FT) level less than 0.22 nmol/L.…”
mentioning
confidence: 99%